Shale Plays Characterization of the Talang Akar Formation in the Jambi Sub-Basin, South Sumatra Basin - Julikah Julikah; Ginanjar Rahmat; Ario Budi Wicaksono; Jakson Anwari (Testing Center for Oil and Gas LEMIGAS, 2020)
The Jambi Sub-Basin is part of the prolifi c South Sumatra Basin which has been proven to produce conventional oil and gas in large quantities. In the basin, Talang Akar Formation (TAF) is believed to be the dominant source rock for commercial hydrocarbons. That means the TAF has potential as shale play resulting oil and gas. Generally, shale plays of the TAF was deposited on littoral-neritic environment during late period of syn-rift until early post-rift at Late Oligocene - Early Miocene. Based on well log analysis, identifi cation characters shale plays of the TAF in the Jambi Sub-Basin have good character as source rock reservoir. Several wells showed that early maturity level happened at depth less than 2000m. Most of TOC, S2 and HI values exist in the range of (1-10) wt%, (0.25 - 10) mg/g rock and (50 - 400) mg HC/ g TOC respectively. Shale plays of the TAF tend to have Type II, II / III and III kerogen. Most of existing wells are not located in the basin center. The geophysical methods such as seismic inversion and seismic attribute can be applied to predict the TOC (Total Organic Carbon) and brittleness index (BI) distributions especially in the basin center. Geologically, the shale plays quality in center of basin was interpreted better than the fl ank. Age of the shale in the Jambi Sub-Basin is relatively much younger when compared to shale in North America. This fact is suspected to cause the TAF shale play to be relatively less brittle. The data processing result shows that the brittleness index values of shale plays tend to be in the range of 40% - 70%.